Effect of phytoliths for mitigating water stress in durum wheat. Issue 1 (10th April 2017) - Meunier, Jean Dominique; Barboni, Doris; Anwar‐ul‐Haq, Muhammad; Levard, Clément; Chaurand, Perrine; Vidal, Vladimir; Grauby, Olivier; Huc, Roland; Laffont‐Schwob, Isabelle; Rabier, Jacques; Keller, Catherine
Summary: The role of silicon (Si) in alleviating biotic and abiotic stresses in crops is well evidenced by empirical studies; however, the mechanisms by which it works are still poorly known. The aim of this study is to determine whether or not phytolith composition and distribution in wheat are affected by drought and, if so, why. Durum wheat was grown using hydroponics in the presence of polyethylene glycol (PEG)‐6000 to perform a water‐stress simulation. We developed an original method for in situ analysis of phytoliths in leaves via X‐ray imaging. PEG was efficient in inhibiting water uptake by roots and creating stress, and prevented a small fraction of Si from being accumulated in the shoots. The application of Si with PEG maintained shoot and root fresh weights (FW) and relative water content at higher values than for plants without Si, especially at PEG 12%. Our data show that, under water stress in the presence of Si, accumulation of phytoliths over the veins provides better support to the leaf, thus allowing for a better development of the whole plant than in the absence of Si. The development of silicified trichomes in durum wheat depends primarily on the availability of Si in soil and is not an adaptation to water stress.